Polyvinyl alcohol film
By using a specific proportion of non-ionic and anionic surfactants and chelating agents in the PVA membrane, the problems of low hydrolysis resistance and fouling resistance of existing PVA membranes are solved, and a PVA membrane preparation with high yield, low optical defects and good peelability are achieved.
Patent Information
- Application Number
- CN202080089892.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-26
- Filing Date
- 2020-12-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-12-24
AI Technical Summary
When using sulfate salt-type anionic surfactant and nitrogen-containing nonionic surfactant, the existing PVA film has low hydrolysis resistance and requires a large increase in the blending amount, resulting in economic and yield problems, and the decomposition is prone to retention and dirt.
The preparation method of polyvinyl alcohol film is adopted, which contains polyvinyl alcohol, non-ionic surfactant (alkanolamide), anionic surfactant and chelating agent (organic carboxylic acid, aminocarbonate and hydroxyaminocarbonate compound). The chelating agent is used to capture the iron element in the film-making stock solution and inhibit the binding reaction between fatty acids and polyvalent metal ions.
A PVA film with excellent yield, few optical defects and good peeling properties is achieved, which prevents the generation of dirt in the production process and improves the economicality and efficiency of the process.
Smart Images

Figure DEST_PATH_IMAGE001 
Figure FDA0005184992290000011 
Figure FDA0005184992290000012
Abstract
Description
Technical Field
[0001] The present invention relates to a polyvinyl alcohol film comprising polyvinyl alcohol (A), a nonionic surfactant (B), an anionic surfactant (C) and a chelating agent (D). Background Art
[0002] Polyvinyl alcohol (hereinafter, sometimes referred to as PVA) films are used for various purposes by utilizing unique properties related to transparency, optical properties, mechanical strength, water solubility, etc. In particular, by utilizing its excellent optical properties, PVA films are used as raw materials (raw films) for manufacturing polarizing films that constitute polarizing plates, which are basic components of liquid crystal displays (LCDs), and their use is expanding. Polarizing plates for LCDs require high optical performance, and polarizing films, which are their components, also require high optical performance.
[0003] Polarizers are usually made by dyeing, uniaxially stretching, and fixing with boron compounds etc. to produce a polarizing film, and then laminating a protective film such as a triacetyl cellulose (TAC) film to the surface of the polarizing film. The original PVA film is usually made by drying a film-making stock solution containing PVA by a casting method or the like.
[0004] So far, there are many known technologies about PVA films or methods for manufacturing them. Patent Document 1 describes a PVA film comprising: a PVA resin, sodium lauryl sulfate as a sulfate ester salt type anionic surfactant (a), polyoxyethylene lauryl ether as an ether type nonionic surfactant (b), and lauric acid diethanolamide as a nitrogen-containing nonionic surfactant (c). Based on this, it is believed that the film has excellent optical properties such as no optical streaks or optical color unevenness, and can exhibit excellent anti-blocking effects.
[0005] In addition, Patent Document 2 discloses a PVA film comprising: a PVA resin, polyoxyethylene lauryl ether as an ether-type nonionic surfactant (a), and polyoxyethylene laurylamine and lauric acid diethanolamide as two nitrogen-containing nonionic surfactants (b). Based on this, it is believed that the film has excellent optical properties such as no optical streaks and can exhibit excellent blocking resistance.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2005-206809;
[0009] Patent document 2: Japanese Patent Application Publication No. 2005-206810. Summary of the invention
[0010] Problems to be solved by the invention
[0011] However, as shown in Patent Document 1, when using sulfate ester salt type anionic surfactants such as sodium lauryl sulfate and nitrogen-containing nonionic surfactants such as lauric acid diethanolamide, due to their low hydrolysis resistance (heat resistance), it is necessary to increase the blending amount in large quantities, and from the perspective of economy, there is room for improvement. In addition, if these surfactants are blended in large quantities, their decomposition products are easily retained and dirt is easily generated in the production process, and from the perspective of productivity, there is also room for improvement. In addition, as shown in Patent Document 2, when using nitrogen-containing nonionic surfactants as surfactants instead of anionic surfactants, in addition to the above-mentioned problems of economy and productivity, there is also the problem of many optical defects in the PVA film.
[0012] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a PVA film having excellent productivity, few optical defects, and good releasability so as to prevent the generation of dirt in the production process.
[0013] Means for solving problems
[0014] The above-mentioned problems are solved by providing a polyvinyl alcohol film, which contains polyvinyl alcohol (A), a nonionic surfactant (B), an anionic surfactant (C) and a chelating agent (D), wherein the nonionic surfactant (B) is an alkanolamide, and the content of the nonionic surfactant (B) is 0.01 to 0.20 parts by mass relative to 100 parts by mass of the polyvinyl alcohol (A), the content of the anionic surfactant (C) is 0.01 to 0.20 parts by mass relative to 100 parts by mass of the polyvinyl alcohol (A), and the chelating agent (D) is at least one compound selected from organic carboxylic acid compounds, amino carbonate compounds and hydroxyamino carbonate compounds, and the content of the chelating agent (D) is 0.005 to 0.20 parts by mass relative to 100 parts by mass of the polyvinyl alcohol (A).
[0015] In this case, the ratio of the number of moles of the chelating agent (D) to the number of moles of the iron element in the polyvinyl alcohol film is preferably 50 times or more. The content of the iron element in the polyvinyl alcohol film is also preferably 0.05 ppm to 1.5 ppm.
[0016] In this case, the film width is preferably 1.5 m or more. The film length is also preferably 3000 m or more. The film thickness is also preferably 10 to 70 μ m.
[0017] Effects of the Invention
[0018] According to the present invention, it is possible to provide a PVA film having excellent productivity, few optical defects, and good releasability, and capable of preventing the generation of dirt in the production process. DETAILED DESCRIPTION
[0019] The PVA film of the present invention contains a certain amount of PVA (A), a specific nonionic surfactant (B), an anionic surfactant (C) and a specific chelating agent (D). The inventors have found that the PVA film containing a certain amount of PVA (A), a nonionic surfactant (B), an anionic surfactant (C) and a chelating agent (D) has few optical defects and good peelability.
[0020] In the past, as nonionic surfactants, alkanolamides such as lauric acid diethanolamide were widely used. However, nonionic surfactants such as alkanolamides and anionic surfactants such as sulfate salts have low heat resistance. Therefore, sometimes they decompose to generate fatty acids, which combine with polyvalent metal ions present in the production process to form fatty acid salts. The fatty acid salts are one of the causes of dirt generated in the production process, and improvement is required. The inventors have conducted in-depth research and found that in addition to containing a certain amount of PVA (A), nonionic surfactant (B), and anionic surfactant (C), a certain amount of specific chelating agent (D) is also contained, thereby preventing the generation of dirt in the production process. Therefore, as shown in the present invention, it is more important to contain a certain amount of PVA (A), a specific nonionic surfactant (B), anionic surfactant (C) and a specific chelating agent (D). By satisfying such a structure, the generation of dirt in the production process can be prevented, so that a PVA film with excellent yield, few optical defects and good peelability can be obtained. It should be noted that in the present invention, the reason for obtaining such a PVA film is presumed to be as follows: since the chelating agent (D) captures the polyvalent metal ions represented by the iron element in the film-forming stock solution, the binding reaction between fatty acids (decomposition products of nonionic surfactants or anionic surfactants) and polyvalent metal ions is suppressed during the film-forming process, and the formation of fatty acid salts is suppressed.
[0021] [PVA (A)]
[0022] As PVA (A), PVA manufactured by saponifying the vinyl ester polymer obtained by polymerizing vinyl ester can be used. As vinyl ester, for example, vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, versatic acid (Versatic Acid) vinyl ester, etc. can be listed. These can be used alone or in combination of two or more, but the former is preferred. From the viewpoints of availability, cost, the yield of PVA (A), as vinyl ester, vinyl acetate is preferred.
[0023] Examples of other monomers copolymerizable with the vinyl ester include: ethylene; olefins having 3 to 30 carbon atoms such as propylene, 1-butene, and isobutylene; acrylic acid or its salts; acrylic acid esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, 2-ethylhexyl acrylate, dodecyl acrylate, and octadecyl acrylate; methacrylic acid or its salts; methacrylic acid esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, 2-ethylhexyl methacrylate, dodecyl methacrylate, and octadecyl methacrylate; acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetoneacrylamide, acrylamidopropanesulfonic acid or its salts, acrylamidopropyldimethylamine or its salts, N-hydroxymethylacrylamide acrylamide derivatives such as amine or its derivatives; methacrylamide derivatives such as methacrylamide, N-methyl methacrylamide, N-ethyl methacrylamide, methacrylamide propanesulfonic acid or its salts, methacrylamide propyl dimethylamine or its salts, N-hydroxymethyl methacrylamide or its derivatives; N-vinylamides such as N-vinyl formamide, N-vinylacetamide, N-vinyl pyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; vinyl cyanides such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or its salts, esters or anhydrides; itaconic acid or its salts, esters or anhydrides; vinyl silyl compounds such as vinyl trimethoxysilane; isopropenyl acetate, etc. These other monomers may be used alone or in combination of two or more. Among them, as the other monomer, ethylene and olefins having 3 to 30 carbon atoms are preferred, and ethylene is more preferred.
[0024] The proportion of the structural units derived from the other monomers in the vinyl ester polymer is not particularly limited, but is preferably 15 mol % or less, more preferably 5 mol % or less, based on the number of moles of the total structural units constituting the vinyl ester polymer.
[0025] There is no restriction on the degree of polymerization of PVA (A), but as the degree of polymerization decreases, the film strength tends to decrease, so it is preferably 200 or more, more preferably 300 or more, further preferably 400 or more, and particularly preferably 500 or more. In addition, if the degree of polymerization is too high, the viscosity of the aqueous solution of PVA (A) or the molten PVA (A) increases, and there is a tendency to be difficult to form a film, so it is preferably 10,000 or less, more preferably 9,000 or less, further preferably 8,000 or less, and particularly preferably 7,000 or less. Here, the degree of polymerization of PVA (A) refers to the average degree of polymerization measured according to the description of JIS K6726-1994, which is measured in water at 30°C after re-saponification and purification of PVA (A), and the limiting viscosity [η] (unit: deciliter / g) is measured by the following formula.
[0026] Degree of polymerization = ([η] × 10 4 / 8.29) (1 / 0.62)
[0027] There is no particular limitation on the saponification degree of PVA (A). For example, PVA (A) of 60 mol% or more can be used. From the perspective of being used as an original roll film for the manufacture of optical films such as polarizing films, the saponification degree of PVA (A) is preferably 95 mol% or more, more preferably 98 mol% or more, and further preferably 99 mol% or more. Here, the saponification degree of PVA (A) refers to the ratio (mol%) of the molar number of the vinyl alcohol unit possessed by PVA (A) relative to the total molar number of the structural unit (typically a vinyl ester monomer unit) converted into a vinyl alcohol unit by saponification and the vinyl alcohol unit. The saponification degree of PVA (A) can be measured according to the description of JIS K6726-1994.
[0028] PVA (A) can use one type of PVA alone, or can use two or more types of PVA with different polymerization degree, saponification degree, modification degree, etc. in combination. However, if the PVA film contains: PVA with acidic functional groups such as carboxyl and sulfonic acid groups, PVA with acid anhydride groups, PVA with basic functional groups such as amino groups, and their neutralization products, etc., which have functional groups that promote cross-linking reactions, the secondary processability of the PVA film sometimes decreases due to the cross-linking reaction between PVA molecules. Therefore, as shown in the original roll film for optical film manufacturing, when excellent secondary processability is required, it is preferred that the content of PVA with acidic functional groups, PVA with acid anhydride groups, PVA with basic functional groups, and their neutralization products in PVA (A) is less than 0.1% by mass, and more preferably none of them are contained.
[0029] The content of PVA (A) in the above-mentioned PVA film is preferably 50% by mass or more, more preferably 70% by mass or more, and further preferably 85% by mass or more.
[0030] [Nonionic surfactant (B)]
[0031] The content of the nonionic surfactant (B) is 0.01 to 0.20 parts by mass relative to 100 parts by mass of PVA (A). When the content of the nonionic surfactant (B) is less than 0.01 parts by mass, many optical defects are generated in the PVA film, and the peelability is deteriorated. The content of the nonionic surfactant (B) is preferably 0.02 parts by mass or more, and more preferably 0.04 parts by mass or more. On the other hand, when the content of the nonionic surfactant (B) exceeds 0.20 parts by mass, the generation of dirt in the production process cannot be prevented, and the yield decreases. The content of the nonionic surfactant (B) is preferably 0.16 parts by mass or less, and more preferably 0.12 parts by mass or less.
[0032] The nonionic surfactant (B) used in the present invention is an alkanolamide. The type of alkanolamide is not particularly limited, and suitable ones are aliphatic alkanolamides such as lauric acid diethanolamide, oleic acid diethanolamide, and lauric acid monoethanolamide. As the aliphatic alkanolamide, a tertiary amide type aliphatic alkanolamide and a secondary amide type aliphatic alkanolamide can be used.
[0033] In addition, aliphatic alkanolamides having polyethylene oxide can also be suitably used as the nonionic surfactant (B). Examples of the alkanolamides include secondary amide type aliphatic alkanolamides represented by the following formula (I) and tertiary amide type aliphatic alkanolamides represented by the following formula (II).
[0034]
[0035] [In formula (I), R is an alkyl group having 8 to 18 carbon atoms, and the number of polyoxyethylene chains (n) is 2 to 10.]
[0036]
[0037] [In formula (II), R is an alkyl group having 8 to 18 carbon atoms, and the number of polyoxyethylene chains (n) is 2 to 10.]
[0038] In the above formulas (I) and (II), R is an alkyl group having 8 to 18 carbon atoms. The above alkyl group may be a straight chain or a branched chain, preferably a straight chain. When the number of carbon atoms of R (alkyl chain length) is less than 8, many optical defects may occur in the PVA film. The number of carbon atoms of R (alkyl chain length) is preferably 9 or more, more preferably 10 or more. On the other hand, when the number of carbon atoms of R (alkyl chain length) exceeds 18, the number of active agent aggregates is large and the haze value may increase. The number of carbon atoms of R (alkyl chain length) is preferably 15 or less, more preferably 13 or less.
[0039] In the above formulas (I) and (II), the number of polyoxyethylene chains (n) is 2 to 10. When the number of polyoxyethylene chains (n) is less than 2, the number of active agent aggregates is large and the haze value may increase. The number of polyoxyethylene chains (n) is preferably 4 or more. On the other hand, when the number of polyoxyethylene chains (n) exceeds 10, many optical defects may occur in the PVA film. The number of polyoxyethylene chains (n) is preferably 8 or less.
[0040] [Anionic surfactant (C)]
[0041] The content of the anionic surfactant (C) is 0.01 to 0.20 parts by mass relative to 100 parts by mass of PVA (A). If the content of the anionic surfactant (C) deviates from this range, optical defects increase. The content of the anionic surfactant (C) is preferably 0.02 parts by mass or more, more preferably 0.04 parts by mass or more. On the other hand, the content of the anionic surfactant (C) is preferably 0.16 parts by mass or less, more preferably 0.12 parts by mass or less.
[0042] The anionic surfactant (C) is not particularly limited, but is preferably at least one selected from sulfate ester salt type and sulfonate salt type.
[0043] Examples of the sulfuric acid ester salt type include sodium alkyl sulfate, potassium alkyl sulfate, ammonium alkyl sulfate, triethanolamine alkyl sulfate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxypropylene alkyl ether sulfate, sodium polyoxyethylene alkylphenyl ether sulfate, etc. As the alkyl group, an alkyl group having 8 to 20 carbon atoms is preferred, and an alkyl group having 10 to 16 carbon atoms is more preferred.
[0044] Examples of the sulfonate type include sodium alkyl sulfonate, potassium alkyl sulfonate, ammonium alkyl sulfonate, triethanolamine alkyl sulfonate, sodium alkylbenzene sulfonate, disodium dodecyl diphenyl ether disulfonate, sodium alkyl naphthalene sulfonate, disodium alkyl sulfosuccinate, disodium polyoxyethylene alkyl sulfosuccinate, etc. The alkyl group is preferably an alkyl group having 8 to 20 carbon atoms, and more preferably an alkyl group having 10 to 16 carbon atoms.
[0045] The above-mentioned surfactants may be used alone or in combination of two or more. Among them, the anionic surfactant (C) is preferably a sulfate ester salt type from the viewpoint of reducing optical defects.
[0046] [Chelating agent (D)]
[0047] The content of the chelating agent (D) is 0.005 to 0.20 parts by mass relative to 100 parts by mass of PVA (A). In the present invention, the polyvalent metal ions represented by the iron element in the film-making stock solution are captured by the chelating agent (D), so that the binding reaction between fatty acids (decomposition products of nonionic surfactants (B) or anionic surfactants (C)) and polyvalent metal ions is suppressed in the film-making process, and the formation of fatty acid salts is suppressed. When the content of the chelating agent (D) is less than 0.005 parts by mass, the generation of dirt in the production process (film-making process) cannot be prevented, and the yield decreases. The content of the chelating agent (D) is preferably 0.007 parts by mass or more, and more preferably 0.01 parts by mass or more. On the other hand, when the content of the chelating agent (D) exceeds 0.20 parts by mass, optical defects increase. The content of the chelating agent (D) is preferably 0.15 parts by mass or less, and more preferably 0.1 parts by mass or less.
[0048] In addition, it is preferred that the ratio of the number of moles of the chelating agent (D) to the number of moles of the iron element in the PVA film is 50 times or more. By making this ratio 50 times or more, the generation of dirt in the production process can be fully prevented. This ratio is more preferably 80 times or more, and further preferably 100 times or more. On the other hand, this ratio is usually 500 times or less.
[0049] The chelating agent (D) in the present invention is at least one compound selected from organic carboxylic acid compounds, amino carbonate compounds and hydroxy amino carbonate compounds. That is, the chelating agent (D) in this specification refers to a compound that combines with a polyvalent metal ion to form a chelate compound, and is at least one compound selected from organic carboxylic acid compounds, amino carbonate compounds and hydroxy amino carbonate compounds.
[0050] An organic carboxylic acid compound refers to a compound or a salt thereof having at least one group selected from two or more carboxyl groups and a hydroxyl group, at least one of which is a carboxyl group. Examples of organic carboxylic acid compounds include aliphatic, alicyclic, and aromatic carboxylic acids, or salts thereof, of which aliphatic carboxylic acids or salts thereof are suitable. Examples of aliphatic carboxylic acids or salts thereof include aliphatic dicarboxylic acids or salts thereof such as oxalic acid, malonic acid, succinic acid, glutaric acid, and adipic acid; aliphatic hydroxycarboxylic acids or salts thereof such as lactic acid, tartaric acid, citric acid, and gluconic acid; ether carboxylic acids or salts thereof such as sodium carboxymethyl propanol dicarboxylate and sodium carboxymethoxysuccinate. Among them, from the perspective of solubility in the film-forming stock solution and effective capture of polyvalent metal ions bound to fatty acids, aliphatic hydroxycarboxylic acids or salts thereof are suitable, citric acid or salts thereof are more suitable, and sodium citrate is further suitable.
[0051] The aminocarbonate compound refers to a compound or a salt thereof having 2 to 6 carboxyl groups in the molecule and at least one secondary amine structure or tertiary amine structure. Examples of the aminocarbonate compound having a secondary amine structure include iminodiacetic acid or a salt thereof. Examples of the aminocarbonate compound having a tertiary amine structure include nitrilotriacetic acid, ethylenediaminetetraacetic acid, diethylenetriaminopentaacetic acid or a salt thereof. Among them, as the aminocarbonate compound, a compound or a salt thereof having 2 to 6 carboxyl groups in the molecule and at least one tertiary amine structure is suitable. From the viewpoint of solubility in the membrane stock solution and effective capture of polyvalent metal ions bound to fatty acids, sodium nitrilotriacetate is more suitable.
[0052] Hydroxyamino carbonate compounds refer to compounds or their salts in which a part or all of the carboxyl groups of the above-mentioned amino carbonate compounds are replaced with hydroxyl groups. As hydroxyamino carbonate compounds, hydroxyethylglycine, triethanolamine, N-(2-hydroxyethyl)iminodiacetic acid, hydroxyethylethylenediaminetetraacetic acid, diethanolamine or their salts can be cited. Among them, from the viewpoint of solubility in the film-making stock solution and effectively capturing the polyvalent metal ions combined with fatty acids, it is suitable that all of the carboxyl groups of the above-mentioned amino carbonate compounds are replaced with hydroxyl groups or their salts, and triethanolamine is more suitable.
[0053] [PVA film]
[0054] The content of iron in the PVA film is preferably 0.05ppm to 1.5ppm. In the present invention, the content of iron in the PVA film is measured by the method described below. Here, with respect to the iron in the PVA film, the iron that forms a salt with a fatty acid (a decomposition product of a nonionic surfactant (B) or an anionic surfactant (C)) and the iron captured by a chelating agent (D) can be measured without distinction. Therefore, the content of iron in the PVA film of the present invention is usually the same as the content of iron in the film-making stock solution. Therefore, when the content of iron in the PVA film is less than 0.05ppm, the purification of the raw material PVA in the film-making stock solution requires a lot of cost, and the economic efficiency may deteriorate. The content is more preferably 0.1ppm or more. On the other hand, when the content of iron in the PVA film exceeds 1.5ppm, it may not be possible to fully prevent the generation of dirt in the production process. In addition, a large amount of chelating agent (D) for capturing the iron in the film-making stock solution needs to be mixed, which is not preferred from the viewpoint of economic efficiency. The content is more preferably 1.0ppm or less.
[0055] From the viewpoint of imparting flexibility to the PVA film, the PVA film of the present invention preferably contains a plasticizer. Preferred plasticizers include polyols, specifically, ethylene glycol, glycerol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, etc. These may use only one plasticizer, or may use two or more plasticizers in combination. Among them, from the viewpoint of compatibility with PVA (A) or availability, ethylene glycol or glycerol is preferred.
[0056] The content of the plasticizer is preferably in the range of 1 to 30 parts by mass relative to 100 parts by mass of PVA (A). If the content of the plasticizer is 1 part by mass or more, problems are less likely to occur in mechanical properties such as impact strength or process qualification during secondary processing. On the other hand, if the content of the plasticizer is 30 parts by mass or less, the film becomes appropriately soft and the workability is improved.
[0057] The PVA film of the present invention may further contain other components except PVA, surfactant and plasticizer as required. As such other components, for example, water, antioxidant, ultraviolet absorber, lubricant, colorant, filler (inorganic particles / starch, etc.), preservative, mildewproof agent, other macromolecular compounds except the above components, etc. can be listed. The content of other components in the PVA film is preferably below 10% by mass.
[0058] The width of the PVA film of the present invention is not particularly limited. Considering the wide polarizing film required in recent years, the width is preferably 1.5 m or more. In addition, if the width of the PVA film is too wide, the manufacturing cost of the film-making device used to manufacture the PVA film increases, and when using a practical manufacturing device to manufacture an optical film, it is sometimes difficult to stretch it uniformly, so the width of the PVA film is usually 7.5 m or less.
[0059] The shape of the PVA film of the present invention is not particularly limited. From the perspective of being able to continuously and smoothly manufacture a more uniform PVA film, or being continuously used when manufacturing an optical film, etc., it is preferably a long film. The length (length in the flow direction) of the long film is not particularly limited and can be appropriately set. The length of the film is preferably more than 3000m. On the other hand, the length of the film is preferably less than 30000m. The long film is preferably wound on a core, etc. to form a film roll.
[0060] The thickness of the PVA film of the present invention is not particularly limited and can be appropriately set. From the viewpoint of using it as a raw film for producing an optical film such as a polarizing film, the thickness of the film is preferably 10 to 70 mm. μ In addition, the thickness of a PVA film can be calculated|required as the average value of the value measured at arbitrary 10 places.
[0061] The method for producing the PVA film of the present invention is not particularly limited. A suitable method is a method for producing a polyvinyl alcohol film containing polyvinyl alcohol (A), a nonionic surfactant (B), an anionic surfactant (C) and a chelating agent (D), comprising the following steps: a step of mixing polyvinyl alcohol (A), a nonionic surfactant (B), anionic surfactant (C) and a chelating agent (D) to prepare a film-forming stock solution; and a step of using the film-forming stock solution to form a film, wherein the nonionic surfactant (B) is an alkanolamide, and the chelating agent (D) is selected from organic carboxylic acid-based compounds. The present invention relates to a film-forming stock solution comprising at least one compound selected from the group consisting of a polyvinyl alcohol compound, an amino carbonate compound and a hydroxyamino carbonate compound. The amount of the nonionic surfactant (B) in the film-forming stock solution is 0.01 to 0.20 parts by mass relative to 100 parts by mass of the polyvinyl alcohol (A). The amount of the anionic surfactant (C) in the film-forming stock solution is 0.01 to 0.20 parts by mass relative to 100 parts by mass of the polyvinyl alcohol (A). The amount of the chelating agent (D) in the film-forming stock solution is 0.005 to 0.20 parts by mass relative to 100 parts by mass of the polyvinyl alcohol (A).
[0062] In the process of preparing the membrane-forming stock solution, a liquid medium may be further mixed. Examples of the liquid medium at this time include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, glycerol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, ethylenediamine, diethylenetriamine, etc., and one or more of these can be used. Among them, water is preferred in terms of low environmental load and recyclability.
[0063] In the method for producing the PVA film of the present invention, for example, a film-making stock solution containing PVA (A), a nonionic surfactant (B), an anionic surfactant (C), a chelating agent (D), a liquid medium, and further containing the above-mentioned plasticizer or other components as required can be used, using known methods such as a cast film-making method or a melt extrusion film-making method. It should be noted that the film-making stock solution can be a stock solution formed by dissolving PVA (A) in a liquid medium, or a stock solution obtained by melting PVA (A).
[0064] The volatility of the film-forming stock solution (the proportion of volatile components such as the liquid medium removed by volatilization or evaporation during film formation in the film-forming stock solution) also varies depending on the film-forming method, film-forming conditions, etc., and is preferably in the range of 50 to 90% by mass, and more preferably in the range of 55 to 80% by mass. By making the volatility of the film-forming stock solution 50% or more by mass, the viscosity of the film-forming stock solution will not be too high and film formation will be easy. On the other hand, by making the volatility of the film-forming stock solution 90% or less by mass, the viscosity of the film-forming stock solution will not be too low, and the thickness uniformity of the resulting PVA film will be improved.
[0065] The blending amount of the nonionic surfactant (B) in the film-forming stock solution is preferably 0.01 to 0.20 parts by mass relative to 100 parts by mass of polyvinyl alcohol (A). When the blending amount of the nonionic surfactant (B) is less than 0.01 parts by mass, many optical defects may occur in the PVA film and the peelability may deteriorate. The blending amount of the nonionic surfactant (B) is more preferably 0.02 parts by mass or more, and further preferably 0.04 parts by mass or more. On the other hand, when the blending amount of the nonionic surfactant (B) exceeds 0.20 parts by mass, it may not be possible to prevent the generation of dirt in the production process. The blending amount of the nonionic surfactant (B) is more preferably 0.16 parts by mass or less, and further preferably 0.12 parts by mass or less. The nonionic surfactant (B) used in the present invention may be used alone or in combination of two or more.
[0066] The blending amount of the anionic surfactant (C) in the above-mentioned film-forming stock solution is preferably 0.01 to 0.20 parts by mass relative to 100 parts by mass of polyvinyl alcohol (A). If the blending amount of the anionic surfactant (C) deviates from this range, the optical defects may increase. The blending amount of the anionic surfactant (C) is more preferably 0.02 parts by mass or more, and further preferably 0.04 parts by mass or more. On the other hand, the blending amount of the anionic surfactant (C) is more preferably 0.16 parts by mass or less, and further preferably 0.12 parts by mass or less. The anionic surfactant (C) used in the present invention may be used alone or in combination of two or more.
[0067] The blending amount of the chelating agent (D) in the above-mentioned film-forming stock solution is preferably 0.005 to 0.20 parts by mass relative to 100 parts by mass of polyvinyl alcohol (A). When the blending amount of the chelating agent (D) is less than 0.005 parts by mass, it may not be possible to prevent the generation of dirt in the production process. The blending amount of the chelating agent (D) is more preferably 0.007 parts by mass or more, and further preferably 0.01 parts by mass or more. On the other hand, when the blending amount of the chelating agent (D) exceeds 0.20 parts by mass, optical defects may increase. The blending amount of the chelating agent (D) is more preferably 0.15 parts by mass or less, and further preferably 0.1 parts by mass or less. The chelating agent (D) used in the present invention may be used alone or in combination of two or more.
[0068] Next, the process of film making is described. Using the above-mentioned film-making stock solution, by a casting film-making method or a melt extrusion film-making method, it is suitable to manufacture the PVA film of the present invention. There is no particular limitation on the specific manufacturing method at this time. For example, the film-making stock solution can be cast or sprayed onto a support such as a drum or a belt to form a film, and then dried on the support to obtain it. For the obtained film, a drying roller or a hot air drying device can be further dried, or a heat treatment device can be used to perform heat treatment, or a humidity conditioning device can be used to perform humidity conditioning as needed. The manufactured PVA film is preferably wound on a core, etc. to form a film roll. In addition, the two ends in the width direction of the manufactured PVA film can be cut off.
[0069] The PVA film of the present invention can be suitably used as a raw film for manufacturing polarizing films, phase difference films, special light-concentrating films, etc. According to the present invention, a PVA film with high light transmittance and high quality can be obtained. Therefore, a suitable embodiment of the present invention is an optical PVA film.
[0070] A suitable embodiment of the present invention is: a method for manufacturing a polarizing film having a step of dyeing the above-mentioned PVA film and a step of stretching. The manufacturing method may further have a fixing treatment step, a drying treatment step, a heat treatment step, etc. There is no particular limitation on the order of dyeing and stretching, and the dyeing treatment may be performed before the stretching treatment, at the same time as the stretching treatment, or after the stretching treatment. In addition, the steps of stretching, dyeing, etc. may be repeated multiple times. In particular, if the stretching is divided into two or more stages, it is easy to perform uniform stretching, so it is preferred.
[0071] As dyes for dyeing the PVA film, iodine or dichroic organic dyes (for example, direct black 17, 19, 154; direct brown 44, 106, 195, 210, 223; direct red 2, 23, 28, 31, 37, 39, 79, 81, 240, 242, 247; direct blue 1, 15, 22, 78, 90, 98, 151, 168, 202, 236, 249, 270; direct violet 9, 12, 51, 98; direct green 1, 85; direct yellow 8, 12, 44, 86, 87; direct orange 26, 39, 106, 107 and other dichroic dyes) can be used. These dyes can be used alone or in combination of two or more. Dyeing can usually be performed by immersing the PVA film in a solution containing the above-mentioned dyes, but there is no particular limitation on the treatment conditions or treatment methods.
[0072] As methods for stretching the PVA film, there are: uniaxial stretching method and biaxial stretching method, and the former is preferred. The uniaxial stretching of stretching the PVA film along the flow direction (MD) or the like can be performed by any method of a wet stretching method or a dry heat stretching method, but from the perspective of the stability of the performance and quality of the resulting polarizing film, the wet stretching method is preferred. As wet stretching methods, there are: methods of stretching the PVA film in pure water, aqueous solutions containing various components such as additives or water-soluble organic solvents, or aqueous dispersions in which various components are dispersed. Specific examples of uniaxial stretching methods based on the wet stretching method include: methods of uniaxial stretching in warm water containing boric acid, methods of uniaxial stretching in a solution containing the above-mentioned dye or in a fixing treatment bath described later, and the like. In addition, the PVA film after absorbing water can be uniaxially stretched in the air, or uniaxially stretched by other methods.
[0073] The stretching temperature during uniaxial stretching is not particularly limited. In the case of wet stretching, a temperature in the range of preferably 20 to 90°C, more preferably 25 to 70°C, and further preferably 30 to 65°C is used. In the case of dry heat stretching, a temperature in the range of preferably 50 to 180°C is used.
[0074] Regarding the stretching ratio of the uniaxial stretching treatment (the total stretching ratio in the case of uniaxial stretching in multiple stages), from the perspective of polarization performance, it is preferred to stretch the film as much as possible before it is about to break, specifically, preferably 4 times or more, more preferably 5 times or more, and further preferably 5.5 times or more. There is no particular upper limit to the stretching ratio, as long as the film does not break, and in order to perform uniform stretching, it is preferably 8.0 times or less.
[0075] When manufacturing a polarizing film, in order to make the adsorption of the dye on the uniaxially stretched PVA film firm, it is preferably fixed. As a fixing treatment, the PVA film can be immersed in a common treatment bath added with boric acid and / or a boron compound. At this time, an iodine compound can be added to the treatment bath as needed.
[0076] It is preferred that the PVA film subjected to uniaxial stretching, or uniaxial stretching and fixing is then dried or heat treated. The temperature of the drying or heat treatment is preferably 30 to 150°C, particularly preferably 50 to 140°C. If the temperature is too low, the dimensional stability of the resulting polarizing film is likely to decrease. On the other hand, if the temperature is too high, the polarization performance is likely to decrease due to the decomposition of the dye, etc.
[0077] A polarizing plate can be prepared by laminating an optically transparent protective film having mechanical strength to both sides or one side of the polarizing film obtained by the above operation. As the protective film in this case, triacetyl cellulose (TAC) film, cellulose acetate / butyrate (CAB) film, acrylic film, polyester film, etc. are used. In addition, as an adhesive for laminating the protective film, a PVA adhesive or an urethane adhesive is generally used, among which a PVA adhesive is preferably used.
[0078] The polarizing plate obtained as described above can be used as a component of a liquid crystal display device by being bonded to a glass substrate after being coated with an acrylic adhesive or the like. When bonding the polarizing plate to a glass substrate, a retardation film, a viewing angle enlarging film, a brightness enhancing film, etc. can be bonded simultaneously. Example
[0079] Hereinafter, the present invention will be specifically described by way of examples etc., but the present invention is not limited to these examples at all.
[0080] [Iron content in PVA film]
[0081] 0.5g PVA film is loaded into a PTFE pressure vessel, 6mL concentrated nitric acid is added thereto, and decomposed at room temperature for 30 minutes. After decomposition, the lid is closed, and a wet decomposition device ("MWS-2" of ACTAC company) is used to heat at 150°C for 10 minutes, then at 180°C for 5 minutes, so as to further decompose, and then cool to room temperature. The treatment solution is transferred to a 100mL volumetric flask (PMP system), constant volume with pure water, and a sample solution for determination is prepared. For the sample solution, the content of iron element is obtained using an ICP emission spectrophotometer ("OPTIMA4300DV" of PerkinElmer company).
[0082] [Chelating agent content in PVA film]
[0083] A 10-meter area was cut from the surface side of the PVA film roll to be measured, and a 100-mm-thick MD100-mm-thick TD100-mm-thick (60-mm-thick) area was collected from an arbitrary position. μ The collected samples were pre-treated according to the following conditions.
[0084] (Pretreatment conditions)
[0085] 1. Accurately weigh 0.3g of sample into a 50ml sample tube;
[0086] 2. Add 15 ml HFIP (hexafluoroisopropanol), then add 1 ml 0.01 mol / l hydrochloric acid, stir and dissolve at 50°C;
[0087] 3. After dissolution, cool to room temperature, and add dropwise to 60 ml of methanol at room temperature with stirring for reprecipitation;
[0088] 4. Filter through a cotton plug to remove sediment;
[0089] 5. Concentrate the filtrate using an evaporator (40°C);
[0090] 6. Add a solution of methanol and water in a ratio of 4:6 and adjust the volume to 2 ml to prepare the analytical sample.
[0091] (Quantification of Chelating Agent)
[0092] The pretreated sample was quantified by HPLC to determine the content of the chelating agent (D). If the signal-to-noise ratio of the chelating agent was inappropriate, the amount of the added solution in the pretreatment condition 6 above or the injection amount in the HPLC measurement was adjusted to quantify the chelating agent.
[0093] (HPLC determination conditions of trisodium citrate and sodium nitrilotriacetate)
[0094] ・Device: ACQUITY UPLC H-class (manufactured by Waters);
[0095] ・Column: ACQUITY UPLC BEH Amide 2.1×100mm 1.7 μ m (waters manufacturing);
[0096] ・Mobile phase: a solution prepared by mixing 0.1% trifluoroacetic acid and acetonitrile in a ratio of 4:6;
[0097] ・Flow rate: 0.5ml / min;
[0098] ・Temperature: 40℃;
[0099] ・Injection volume: 10 μ L;
[0100] ・Detector: ELSD.
[0101] (HPLC determination conditions of triethanolamine)
[0102] ・Device: LC-20a1 (manufactured by Shimadzu Corporation);
[0103] ・Column: TSKgel Amide-80 (4.6×250mm, 5 μ m);
[0104] ・Mobile phase: a mixture of 0.1% formic acid and acetonitrile;
[0105] ・Gradient time and acetonitrile concentration of mobile phase:
[0106] [Table 1]
[0107] Time (minutes) 0 5 15 16 20 Acetonitrile concentration (%) 90 20 20 90 stop
[0108] ・Flow rate: 1ml / min;
[0109] ・Temperature: 40℃;
[0110] ・Injection volume: 10 μ L;
[0111] ・Detector: corona.
[0112] [Qualification of PVA film manufacturing process]
[0113] (Peelability)
[0114] In the film production of long films of more than 4000 m, when the film was peeled off from the casting drum, a film that could be peeled off without any problem was evaluated as A, a film that was easily peeled off although partially adhered to the drum and had no problem with the yield was evaluated as B, and a film that adhered to the drum and could not be peeled off was evaluated as C.
[0115] [Quality of PVA film]
[0116] (Evaluation method of optical defects)
[0117] The streak defects and shark skin defects on the PVA film that are parallel to the flow direction (MD direction) during film formation were visually observed and evaluated. Specifically, the sample pieces cut from the PVA film obtained in the following examples and comparative examples were hung vertically in the MD direction, a 30W straight tube fluorescent lamp was placed vertically behind it and lit, and the optical defects were evaluated according to the following criteria.
[0118] A: There are absolutely no stripe or shark skin defects, which is the most suitable level for the product;
[0119] B: Although there are some stripe-like or shark skin-like defects, the product is acceptable.
[0120] C: There are many streaky or sharkskin-like defects, which is not suitable for the product level.
[0121] [Die head dirt]
[0122] After 50,000 m of PVA film was continuously produced, the equipment was stopped, and the adhesion state of the dirt on the raw liquid flow path inside the die was observed and evaluated according to the following criteria.
[0123] A: No dirt, which is the most suitable level for product collection;
[0124] B: Although there is some dirt, it is at a level that can be used for product collection;
[0125] C: There is a lot of dirt, and the level is not suitable for product collection.
[0126] Example 1
[0127] As PVA (A), a small chip of PVA (saponified product of homopolymer of vinyl acetate) having a polymerization degree of 2400 and a saponification degree of 99.9 mol % was used. 100 parts by mass of the small chip of PVA was immersed in 2500 parts by mass of distilled water at 35° C. and then centrifuged to obtain a PVA water-containing small chip having a volatility of 60% by mass.
[0128] 250 parts by mass of the PVA water-containing flakes (100 parts by mass of dry PVA) were mixed with 25 parts by mass of distilled water, 12 parts by mass of glycerol, 0.05 parts by mass of a nonionic surfactant (B), 0.05 parts by mass of anionic surfactant (C), and 0.03 parts by mass of a chelating agent (D), and the resulting mixture was heated and melted using a twin-screw extruder (maximum temperature 130° C.) to prepare a film-forming stock solution. The nonionic surfactant (B) used at this time was tertiary amide type lauric acid diethanolamide, the anionic surfactant (C) was sodium polyoxyethylene lauryl ether sulfate (the number of carbon atoms in the alkyl group was 12 and the number of ethylene oxide additions was 3), and the chelating agent (D) was sodium citrate.
[0129] The film-forming stock solution was cooled to 100°C by a heat exchanger, and then extruded from a coathanger die with a width of 180 cm onto a drum with a surface temperature of 90°C to form a film. The film was then dried using a hot air drying device. The two ends of the film thickened by shrinkage during film formation were cut off, thereby continuously producing a film with a thickness of 60 cm. μ m, 165 cm wide PVA film. The peelability of the PVA film in the manufacturing process was evaluated using the above method. Then, a 4000 m long portion of the manufactured PVA film was wound on a cylindrical core to form a film roll. The optical defects and iron content of the obtained PVA film were evaluated using the above method. In addition, the dirt attached to the die head during the manufacturing process was evaluated using the above method. The results are shown in Table 2.
[0130] Examples 2 to 7, Comparative Examples 1 to 6
[0131] The same operation as in Example 1 was performed to produce and evaluate a PVA film except that the types and amounts of the nonionic surfactant (B), anionic surfactant (C) and chelating agent (D) were changed as shown in Table 2. It should be noted that the chelating agent (D) used in Example 3 was triethanolamine, the chelating agent (D) used in Example 4 was sodium nitrilotriacetate, and the nonionic surfactant (B) and anionic surfactant (C) used in Example 5 were polyoxyethylene lauric acid monoethanolamide (polyoxyethylene chain number was 6) and sodium alkyl sulfonate (alkyl carbon number was 15), respectively.
[0132] As shown in Table 2, the PVA films of Examples 1 to 7 have excellent peelability, few optical defects, and good quality. In addition, there is no die dirt, so the frequency of die cleaning can be less, and the yield is excellent. On the other hand, the PVA film of Comparative Example 1 with a large amount of nonionic surfactant (B) has a lot of die dirt. The PVA films of Comparative Example 2 with a large amount of anionic surfactant (C) and Comparative Example 3 with a large amount of chelating agent (D) have many optical defects. The PVA film of Comparative Example 4 that does not contain a nonionic surfactant (B) has poor peelability and also has many optical defects. The PVA film of Comparative Example 5 that does not contain anionic surfactant (C) has many optical defects. The PVA film of Comparative Example 6 that does not contain a chelating agent (D) has a lot of die dirt. It should be noted that, as shown in Table 2, the blending amount values of the nonionic surfactant (B) and the anionic surfactant (C) in the film-making solution of the PVA film are consistent with the content values of the nonionic surfactant (B) and the anionic surfactant (C) in the PVA film. This is because: the fatty acids generated by the decomposition of the nonionic surfactant (B) and the anionic surfactant (C) blended in the film-making solution are very small, so the difference between the blending amount value and the content value cannot be measured.
[0133] [Table 2]
[0134]
Claims
1. A polyvinyl alcohol film comprising polyvinyl alcohol (A), a nonionic surfactant (B), an anionic surfactant (C) and a chelating agent (D), in, The nonionic surfactant (B) is a secondary amide type aliphatic alkanolamide represented by the following formula (I) or a tertiary amide type aliphatic alkanolamide represented by the following formula (II), In formula (I), R is an alkyl group having 8 to 18 carbon atoms, n is the number of polyoxyethylene chain segments, and n is 2 to 10. In formula (II), R is an alkyl group having 8 to 18 carbon atoms, n is the number of polyoxyethylene chain segments, and n is 2 to 10. The content of the nonionic surfactant (B) is 0.05 to 0.10 parts by mass relative to 100 parts by mass of the polyvinyl alcohol (A). The anionic surfactant (C) is a sulfate ester type, The content of the anionic surfactant (C) is 0.05 to 0.10 parts by mass relative to 100 parts by mass of the polyvinyl alcohol (A). The chelating agent (D) is at least one compound selected from the group consisting of organic carboxylic acid compounds, amino carbonate compounds, and hydroxyamino carbonate compounds. The content of the chelating agent (D) is 0.006 to 0.030 parts by mass relative to 100 parts by mass of the polyvinyl alcohol (A).
2. The polyvinyl alcohol film according to claim 1, wherein The ratio of the number of moles of the chelating agent (D) to the number of moles of the iron element in the polyvinyl alcohol film is 50 times or more.
3. The polyvinyl alcohol film according to claim 1 or 2, wherein The content of iron in the polyvinyl alcohol film is 0.05 ppm to 1.5 ppm. The polyvinyl alcohol film according to claim 1 or 2, which has a width of 1.5 m or more. The polyvinyl alcohol film according to claim 1 or 2, which has a length of 3000 m or more. 6 . The polyvinyl alcohol film according to claim 1 , wherein the polyvinyl alcohol film has a thickness of 10 to 70 μm.
Citation Information
Patent Citations
Polyvinyl alcohol-based film and use of the same
JP2005206809A
Polyvinyl alcohol-based film and use of the same
JP2005206810A
Laundry sheet and production process thereof
CN107177423A